THE EFFECT OF QUIZIZZ ON STUDENTS’ READING COMPREHENSION OF GRADE X AT SMK SWASTA PAB 1 HELVETIA ACADEMIC YEAR 2023-2024 - Ningsih, Nur Widya; Rahmawati, Wiki Tedi; Lubis, Sofia Idawati (FKIP Universitas Al Washliyah Medan, 2024)
This research aimed to find out whether the use of quizizz gave significant effect or not on students’ reading comprehension. The research was designed as a quasi-experimental with quantitative approach. The population of this research was the tenth-grade students of SMK SWASTA PAB 1 Helvetia. The sample was two parallel class namely X-Tbsm 1 which consisted of 30 students as the control class and X-Tbsm 2 which consisted of 30 students as the experimental class. Both classes were given pre-test and post-test. The experimental class was given treatment using Quizizz. Data analysis employed SPSS 29. Pre-test results for the experimental group were 62.67, whereas those for the control group were 60.00. while the experimental class's post-test score was 80.00 and the control classes was 70.33. Calculating the T-test revealed a significant difference. The analysis finding revealed that the sig (2-tailed) value was 0.01< 0.05, indicating that H0 was rejected and Ha was approved. As a result, it was possible to draw the conclusion that Quizizz gave a significant effect on students’ reading comprehension, particularly the descriptive text. Keywords: Quizizz, Reading Comprehension, Descriptive Text